STUDI KASUS MANAJEMEN PRODUKSI USAHA KONVEKSI PADA MUTHIA KONVEKSI DI TANJUNG BERINGIN PASAMAN - Mardatillah, Azzahra Fujiatul; Suci, Puji Hujria (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
One of the industries in the clothing sector is convection. In Nagari Tanjung Beringin, Lubuk Suhuing District, Pasaman Regency, there is a convection, namely Muthia Konveksi. Muthia Konveksi was founded in 2005 in Batam, then in 2020 this convection moved to Tanjung Beringin. Muthia Konveksi produces ready-to-wear products in the form of sports t-shirts, office uniforms, and other men's and women's clothing. This research aims to describe production management in the Muthia Konveksi business in the form of planning, organizing and production processes.The research method used is a qualitative descriptive method. This research was conducted in Nagari Tanjung Beringin, Pasaman Regency, precisely at the Muthia Konveksi business which is located on Pasar Benteng Baru street, No. 67, Tanjung Beringin village, Lubuk Sikaping District, Pasaman Regency. The types of data are primary data and secondary data. Data collection techniques are through observation, interviews and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the research at Muthia Konveksi include planning before production is carried out, organization at Muthia Konveksi and the production process at Muthia Konveksi